Multipoint Nonlocal Problem for Ordinary Differential Equations - Faris, Fahmi Sharif (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Boundary value problems with nonlocal boundary conditions have been considered in numerous investigations.In this thesis different approaches are analyzed by considering nonlocal boundary conditions of the solution of second order ordinary differential equations. For the existences and uniqueness of the solution the method of contraction mapping of the multipoint nonlocal problems is applied. The finite-difference analogue of the method is also discussed. Keywords: Boundary Value Problems , Second order ordinary differential equations, multipoint nonlocal condition.

ÖZ: Yerel olmayan sınır koşulları ile Sınır değer problemleri sayısız araştırmalarda dikkate alınmıştır. Bu tez çalışmasında farklı yaklaşımlar ikinci mertebeden adi diferansiyel denklemlerin çözümünün yerel olmayan sınır koşullarını dikkate alınarak analiz edilmektedir. Çözümün varoluşunun ve teklik çoklu yerel olmayan problemlerin daralma haritalama yöntemi uygulanır. Yöntemin sonlu farklar analogu da tartışılmıştır. Anahtar Kelimeler: Sınır Değer Problemleri, İkinci mertebeden adi diferansiyel denklemler, çoklu yerel olmayan Sınır Problemleri.
Master of Science in Mathematics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2015. Supervisor: Prof. Dr. Adiguzel Dosiyev.
Keywords: Mathematics; Differential equations; Boundary Value Problems; Second order ordinary differential equations; multipoint nonlocal condition Remove selected